Analisis Hukum Keluarga Islam terhadap Penetapan Nomor: 51/Pdt.P/2024/PA:Prw tentang Penolakan Dispensasi Kawin Akibat Penggerebekan - Muhammad Taufiqurrahman; Marwin Marwin; Ahmad Burhanuddin; Jayusman Jayusman (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Studies on marriage dispensation in Indonesia have predominantly focused on the factors underlying the approval of applications and the social reasons contributing to child marriage practices. Previous research tends to position marriage dispensation as a legal solution to social and moral pressures, while studies that specifically examine the rejection of marriage dispensation and its implications for strengthening child protection within the framework of Islamic family law remain relatively limited. This condition reveals a research gap, particularly concerning the shifting paradigm of religious court decisions that increasingly prioritize the best interests of the child as a primary consideration. This study aims to analyze the judges’ legal reasoning in rejecting a marriage dispensation application in the Decision of the Pringsewu Religious Court Number 51/Pdt.P/2024/PA.Prw and to examine its conformity with the principles of Islamic family law. Employing a normative juridical approach with qualitative descriptive analysis, this research examines court decisions, relevant statutory regulations, and the doctrine of maqāṣid al-sharī‘ah. The analysis focuses on the implementation of Law Number 16 of 2019 and Supreme Court Regulation (PERMA) Number 5 of 2019 in the context of child protection. The findings indicate that the rejection of the marriage dispensation was based on considerations of child protection, continuity of education, psychological readiness, and reproductive health. From the perspective of Islamic family law, the decision reflects the application of maqāṣid al-sharī‘ah, particularly the protection of lineage (ḥifẓ al-nasl). This study concludes that marriage dispensation is not an absolute legal right, but a conditional legal policy that must prioritize public welfare and the best interests of the child.